2014
DOI: 10.1186/1742-2094-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Protection of ischemic post conditioning against transient focal ischemia-induced brain damage is associated with inhibition of neuroinflammation via modulation of TLR2 and TLR4 pathways

Abstract: Background and purposeIschemic postconditioning has been demonstrated to be a protective procedure to brain damage caused by transient focal ischemia/reperfusion. However, it is elusive whether the protection of postconditioning against brain damage and neuroinflammation is via regulating TLR2 and TLR4 pathways. In the present study, we examined the protection of ischemic postconditioning performed immediately prior to the recovery of cerebral blood supply on brain damage caused by various duration of ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Microglia express functional TLR229 and TLR330 in addition to TLR4. TLR signaling pathways may be involved in neurodegenerative disorders31, including motor neuron disease32, cerebral hypoxia-ischemia151633 and blood-spinal cord barrier dysfunction after ischemia/reperfusion injury34, along with microglial TLR229 and TLR330 in preclinical pain models. For these experiments zymosan and Pam3CSK4 (TLR2 activators)35 and poly(I:C), an activator of TLR336 were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia express functional TLR229 and TLR330 in addition to TLR4. TLR signaling pathways may be involved in neurodegenerative disorders31, including motor neuron disease32, cerebral hypoxia-ischemia151633 and blood-spinal cord barrier dysfunction after ischemia/reperfusion injury34, along with microglial TLR229 and TLR330 in preclinical pain models. For these experiments zymosan and Pam3CSK4 (TLR2 activators)35 and poly(I:C), an activator of TLR336 were used.…”
Section: Resultsmentioning
confidence: 99%
“…Within this context, the recruitment of TLRs contributes to inflammation by amplifying pro-inflammatory cytokine and other mediator release. TLRs thus play a central role in inflammation's impact on neuronal cell health, and their participation in neuroinflammation and neurological diseases is an area of growing interest, encompassing not only acute and chronic neurodegenerative disorders151632333448, but also neuropathic pain49 and even mood disorders50. ATP appears to be one of the most powerful stimuli to enhance and accelerate IL-1β release, via activation of P2X 7 R and caspase 12223.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, previous studies have shown that IPC suppresses the generation of ROS and the synthesis of pro-inflammatory cytokines during the reperfusion period and decreases cerebral-induced apoptosis [35,36]. Previous studies suggested that IPC reduced post-ischemic release of the cytokines TNF-α and IL-8; accordingly, they indicated that may be a promising neuroprotective strategy achieved by the inhibition of TLR4 pathway mediated inflammatory response [37,38]. Our data agree with these results and confirm that IPC protects against cerebral I/RI through anti-inflammatory and antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…; Wang et al . ), whereas a study by Hua and colleagues (Hua et al . ) showed that TLR2 appears to be neuroprotective by enhancing the activation of protective signaling in response to cerebral ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 87%